2012
DOI: 10.1111/j.1365-2702.2011.04022.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining the needs of ICU patient families in a suburban/rural Greek population: a prospective cohort study

Abstract: Enhanced recognition of these needs may improve quality of care offered by intensive care unit-care team to families of their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 21 publications
6
41
0
Order By: Relevance
“…Compared to Lee and Lau's study (2003), which had a great deal of similarity to the results of our study, the need of "To feel there is hope" was among the top 10 needs of Iranian families, which is concordant with research in Greece, China and Jordan (Chatzaki et al 2012;Lee et al 2000;Omari, 2009). However, it was not among the list of needs reported by Lee and Lau (2003).…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Compared to Lee and Lau's study (2003), which had a great deal of similarity to the results of our study, the need of "To feel there is hope" was among the top 10 needs of Iranian families, which is concordant with research in Greece, China and Jordan (Chatzaki et al 2012;Lee et al 2000;Omari, 2009). However, it was not among the list of needs reported by Lee and Lau (2003).…”
Section: Discussionmentioning
confidence: 51%
“…The need of "To be assured the best possible care is being given to patient" was the second important need of Iranian families; in many similar studies this item has also been reported as an important need (Chatzaki et al 2012;Lee et al 2000;Lau, 2003, Obringer et al 2012;Omari, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations